Sintesis Glikogen Hati dan Otot pada Tikus Diabetes yang Diberi Ekstrak Tempe - Suarsana, I Nyoman; Pontjo, Bambang; Wresdiyati, Tutik; Bintang, Maria (Jurnal Veteriner, 2010)
Glycogen is found at all of body tissue, especially mostly in liver and muscle. The objectives of thisresearch was to evaluate the content of glycogen in liver and muscle of diabetic rats that were treated withextract of tempe. A total of twenty male Spraque Dawley rats of 2 months old were used in this study. Therats were divided into four groups: (1) negative control group (K-), that were not treated extract of tempeand nondiabetic, (2) positif extract of tempe group (ET), that were treated with extract of tempe andnondiabetic (3) positif diabetic group (DM), and (4) diabetic and extract of tempe group (DM+ET). Extractof tempe was orally administered with dose 300 mg/kg bw/day. The treatment was conducted for 28 days.Effect of extract of tempe on body weight of all rats was determined at various time interval at 0, 4, 7, 14,21, and 28 days. At the end of the experiment, all rats were sacrificed by cervical dislocation. Liver andmuscle gastrocnemius were collected for analysis of glycogen level. The result of this study showed thatadministration methanol extract of tempe of 300 mg/kg bw/day can increase body weight, glycogen synthesisin the liver and muscle in normal rats (rat of ET group) and also diabetic rats (rat of DM+ET group). At theend of research, diabetic rats (rat of DM group) were decrease of body weight up to 5.7%. On the rat ofDM+ET group, rat of K(-) group and rat of ET group were increase of body weight of 5.7%, 19.3% and 20.3%,respectively. Glycogen level both liver, and muscle at rat of ET group and rat of DM+ET group wereincrease each of 9.29%, 2.2% in liver and 18.27% and 4.02% in muscle. Glycogen level at rat of DM groupwere decrease up to 42.5% in liver and 31.6% in muscle.
Keywords: Glycogen, tempe, diabetic, liver, muscle gastrocnemius